A preoperative modified Allen test result may be associated with long term mortality after hemodialysis access construction. Issue 1 (January 2022) - Yadav, Reshabh; Gerrickens, Michael WM; van Kuijk, Sander MJ; Teijink, Joep AW; Scheltinga, Marc RM
Background: The modified Allen test (MAT) is a simple bedside method determining collateral hand circulation prior to hemodialysis (HD) access surgery. Hand ischemia as reflected by low systolic finger pressures ( P dig ) is associated with high mortality rates in severe kidney disease (CKD) patients. Aim of the present study was to assess a possible relation between absolute finger pressure drop (∂ P dig ) during a preoperative MAT and mortality after a first HD access construction. Methods: P dig (systolic pressure, mmHg) was measured using digital plethysmography following compression of radial and ulnar arteries in CKD patients just before access surgery between January 2009 and December 2018 in one center. The greatest ∂ P dig of both index fingers was used for analysis. Cardiovascular and overall mortality were assessed during the following 4 years using the ERA-EDTA classification system (codes 11, 14–16, 18, 22–26, 29). Cox regression analysis determined possible associations between ∂ P dig and mortality. Results: Complete data sets were available in 108 patients (male n = 71; age 70 years ±12; mean follow up (FU) 1.6 years ±0.1; FU index 99% ±1). Median ∂ P dig was 31 mmHg (range 0–167 mmHg). Patients having cardiovascular disease (CV+) demonstrated higher ∂ P dig values (CV+ 44 ± 5 mmHg vs CV− 29 ± 3 mmHg, p = 0.012). A total of 26 patients (24%) died during FU (CV+ death, n = 16; 62%). For each 10 mmHg ∂ P dig increase, overall mortality increased by 10%, and CV+ mortality by 15% (overall mortality: HR 1.10 [1.01–1.22], p = 0.048; CV+ mortality: 1.15 [1.03–1.29], p = 0.017). Following correction for age, ∂ P dig remained associated with CV+ mortality (HR 1.13 [1.00–1.26], p = 0.043). Conclusions: A large drop in systolic finger pressure during a preoperative MAT is related to mortality after primary HD access surgery. The role of this potential novel risk parameter requires confirmation in a larger population.